A Case Study Of Huawei Technologies - Jingyi, Shi (2005)
Huawei technologies established in 1988 and headquartered in Shenzhen China, specializes in the research and development, production and marketing of telecom equipment, providing customized network solutions in different telecom fields.A study was undertaken to determine the reasons why workers have the desire to remain employed by an organization.